Viral discovery and diversity in trypanosomatid protozoa with a focus on relatives of the human parasite Leishmania - Grybchuk, Danyil; Akopyants, Natalia S; Kostygov, Alexei Y; Konovalovas, Aleksandras; Lye, Lon-Fye; Dobson, Deborah E; Zangger, Haroun; Fasel, Nicolas; Butenko, Anzhelika; Frolov, Alexander O; Votýpka, Jan; d'Avila-Levy, Claudia M; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Knowledge of viral diversity is expanding greatly, but many lineages remain underexplored. We surveyed RNA viruses in 52 cultured monoxenous relatives of the human parasite Leishmania (Crithidia and Leptomonas), as well as plant-infecting PhytomonasLeptomonas pyrrhocoris was a hotbed for viral discovery, carrying a virus (Leptomonas pyrrhocoris ostravirus 1) with a highly divergent RNA-dependent RNA polymerase missed by conventional BLAST searches, an emergent clade of tombus-like viruses, and an example of viral endogenization. A deep-branching clade of trypanosomatid narnaviruses was found, notable as Leptomonas seymouri bearing Narna-like virus 1 (LepseyNLV1) have been reported in cultures recovered from patients with visceral leishmaniasis. A deep-branching trypanosomatid viral lineage showing strong affinities to bunyaviruses was termed "Leishbunyavirus" (LBV) and judged sufficiently distinct to warrant assignment within a proposed family termed "Leishbunyaviridae" Numerous relatives of trypanosomatid viruses were found in insect metatranscriptomic surveys, which likely arise from trypanosomatid microbiota. Despite extensive sampling we found no relatives of the totivirus Leishmaniavirus (LRV1/2), implying that it was acquired at about the same time the Leishmania became able to parasitize vertebrates. As viruses were found in over a quarter of isolates tested, many more are likely to be found in the >600 unsurveyed trypanosomatid species. Viral loss was occasionally observed in culture, providing potentially isogenic virus-free lines enabling studies probing the biological role of trypanosomatid viruses. These data shed important insights on the emergence of viruses within an important trypanosomatid clade relevant to human disease.
Keywords: Trypanosomatidae; lidé; interakce hostitele a patogenu; Host Specificity; persistent virus infection; Humans; genetická variace; RNA-viry; coevolution; fylogeneze; coinfection; RNA Viruses; infekce prvoky kmene Euglenozoa; hostitelská specificita; Euglenozoa Infections; Trypanosomatina; zvířata; Animals; Host-Pathogen Interactions; Bunyavirales; Phylogeny; Genetic Variation